A formação do pesquisador juvenil: um estudo sob enfoque da competência informacional - Janaina Ferreira Fialho (2004)
This qualitative study aims at analyzing the implications of the use of sources of information in the formative process of the young researcher through the practice of school research. The specific objectives are: to identify the influence of the pedagogical policies of the school in theformation of this researcher, to systematize the developmental methodologies of school research the school employs, to identify the role of the teachers and the library in carrying out school research, as well as the influence of the family in the young researchers formation. To fulfill these objectives, two schools of Belo Horizonte, one public, the other private, were selected. In each school, students, teachers, the librarian, and the pedagogical coordinator were interviewed. The collection of data was made through a semi-structured interview. This study, developed in the area of Information Science, seeks to understand the phenomenon in the light of the theory of information literacy. To develop the problem, it also uses as theoretical support the concept of literacy and learning based on questioning. The study finds that the preparation of the researcher should take place during his entire time at school through the development of specific skills. In this space, family, teacher, classmates and the pedagogical policies of the school are important factors in the formation of the young researcher. Also of fundamental importance are the actions of the librarian and the adequate use of the sources of information. These factors may directly influence the formation of a good researcher if they are more properly measured.